[PS 03-21] THE EPIDEMIOLOGICAL CHARACTERISTIC OF PREHYPERTENSIVE WOMEN IN GANSU PROVINCE OF CHINA. (September 2016) - Zhao, Xu; Meng, Huitao; Zhang, Xiaowei; Wang, Qiongying; Liang, Wei; Zhang, Tiancheng; Yu, Heng; Zhao, Yang; Yu, Jing
Abstract : Objective: To explore the prevalence of prehypertensive women in Gansu Province, and analyze the relationship between blood pressure and cardiovascular diseases and stroke. Design and method: A cross-sectional investigation was carried out in Gansu Province. The total of 14000 female residents were investigated by face-to-face questionnaires, and physical measurements at the same time. All of the investigators and statisticians were well trained before the survey. The results of the questionnaires were statistical analyzed by using SPSS statistics 19.0. Results: The prevalence of high- normal blood pressure was 38.0% in Gansu Province, and the standardized prevalence was 38.4%, with the highest morbidity between 45- 54 and 55- 64 age groups, which were 43.1% and 42.0%. The prevalence of normal blood pressure, hypertension stage 1, hypertension stage 2 and hypertension stage 3 were 34.4%, 19.1%, 6.4% and 2.1% respectively. There were almost 2.9% and 0.8% of individuals with coronary heart disease and stroke. In high-normal blood pressure women, the morbidity of coronary heart disease and stroke were 1.5 times higher in postmenopausal women compared with premenopausal women. In addition, the morbidityof coronary heart disease and stroke were 1.1 times and 1.2 times respectively in postmenopausal hypertensive women compared with premenopausal hypertensive women. Conclusions: The prevalence of female high normal blood pressure in Gansu Province is increasing. The prevention and management of prehypertension in women should also be taken into account to decrease the incidence of cardiovascular complications.